Sosialisasi Keamanan Data Dalam Melindungi Informasi Pribadi Di era Digital - Della Putri Kinanti; Rahmadanti Miliana; Putri Hamidah Tumangger; Muhamad Nurridwan; Arif Frima Ari Suwadji (Jurnal Sinergi Sistem Informasi Pengabdian Masyarakat, 2025)
In the digital era, the rapid growth of information technology has influenced the way people communicate and carry out their daily activities, including students. However, the lack of awareness regarding the importance of protecting personal data increases the risk of data misuse by irresponsible parties. The objective of this Community Service Program (PKM) is to enhance students' digital literacy and their understanding of personal data protection at SMP Islam Ayatra in Tangerang. The activity, held on Saturday, May 24, 2025, employed interactive socialization methods, case discussions, and pre- and post-tests. The results showed that students gained a better understanding of data security concepts, data breach risks, and preventive measures. The post-test results indicated that 85% of participants scored higher than in the pre-test. This program not only improved their knowledge but also taught them to use information technology wisely and critically. Furthermore, the program encouraged the school to integrate digital literacy into sustainable learning. The activity concluded with a group photo session and the presentation of a plaque to the school. It is expected that this initiative will help students safeguard their digital privacy and become responsible technology users.